Fibrillin-1 insufficiency alters periodontal wound healing failure in a mouse model of Marfan syndrome. (June 2018) - Handa, Keisuke; Abe, Syouta; Suresh, V. Venkata; Fujieda, Yoshiyasu; Ishikawa, Masaki; Orimoto, Ai; Kobayashi, Yoko; Yamada, Satoru; Yamaba, Satoko; Murakami, Shinya; Saito, Masahiro
Highlights: At early wound healing stage, Fibrillin-1 expression was induced. Reduced fibrillin-1 expression delayed bone healing in MFS mice. Fibrillin-1 insufficiency interferes with wound healing of periodontal tissue. Abstract: Objective: Marfan syndrome (MFS) is a systemic connective tissue disorder caused by insufficient fibrillin-1 (FBN-1), a major component of microfibrils that controls the elasticity and integrity of connective tissues. FBN-1 insufficiency in MFS leads to structural weakness, which causes various tissue disorders, including cardiovascular and periodontal disease. However, the role of FBN-1 insufficiency in the destruction and regeneration of connective tissue has not yet been clarified. To investigate the role of FBN-1 insufficiency in tissue destruction and regeneration. Design: We used a ligature-induced (LI) periodontal disease model in fbn-1-deficient mice (fbn-1 c1039G/+ mice) with MFS and investigated the regeneration level of periodontal tissue and as an inflamatic marker, the expression of the matrix metalloproteinase (mmp)-9 and tumor necrosis factor (tnf)-α. Results: Interestingly, fbn-1 c1039G/+ mice exhibited slowed wound healing compared with wild type mice, but periodontal tissue destruction did not differ between these mice. Moreover, fbn-1 c1039G/+ mice exhibited delayed bone healing in association with continuous mmp-9 and tnf-α expression. Furthermore, inflammatory cells were obvious even after the removal of ligatures. Conclusion: These data suggest that fibrillin-1 insufficiency in fbn-1 c1039G/+ mice interfered with wound healing in connective tissue damaged by inflammatory diseases such as periodontal disease.